Hind limb osteology of Gracilisuchus stipanicicorum (Archosauria: Pseudosuchia) - Lecuona, Agustina (2011)
Gracilisuchus stipanicicorum Romer, 1972, from the Middle-Late Triassic of the Ischigualasto-Villa Unión Basin of Argentina, is an extinct pseudosuchian archosaur on the stem toCrocodylomorpha. The pelvic girdle and hind limb anatomy of a referred specimen of Gracilisuchusstipanicicorum is described and compared with that from a broad range of archosauriform taxa,including basal members such as crurotarsans and basal ornithodirans. The description of thisspecimen reveals new information on the anatomy of the pelvic girdle and hind limb of Gracilisuchus,through a detailed examination of some anatomical regions barely or not previously described, aswell as reinterpretations of previous features. The phylogenetic affinities of Gracilisuchus within theArchosauria remain to be tested, but Gracilisuchus shares two putative synapomorphies with somenon-crocodyliform crocodylomorphs, providing tentative support for the monophyly of Sphenosuchia(e.g., Sereno & Wild 1992; Wu & Chatterjee 1993) and the close relationship of Gracilisuchusto that clade. These characteristics are: (i) the morphology and poor development of the femoralfourth trochanter, closely resembling the condition of Pseudhesperosuchus and Trialestes; and (ii) apoor anterior development of the femoral head, shared with Pseudhesperosuchus. On the other handthere are characters that reject the inclusion of Gracilisuchus within Crocodylomorpha (Nesbitt2011), such as the absence of an imperforated acetabulum, and that rather suggests a sister-taxonposition to Crocodylomorpha.